Review and analysis of information on the biology and morphology of immature stages of robber flies (Diptera: Asilidae) - Dennis, D. Steve; Barnes, Jeffrey K.; Knutson, Lloyd (Zootaxa, 2013)
Recent publications on the immature stages of robber flies (Asilidae) are reviewed and listed for the 14 currently recognized subfamilies (Asilinae, Bathypogoninae, Brachyrhopalinae, Dasypogoninae, Dioctriinae, Laphriinae, Leptogastrinae, Ommatiinae, Phellinae, Stenopogoninae, Stichopogoninae, Tillobromatinae, Trigonomiminae, and Willistonininae). For the Phellinae there are only limited data on the pupal cases, and for the Tillobromatinae there are only limited data on the eggs (potential oviposition site in soil) and pupal cases. The recent literature is compared with pertinent pre-1972 publications.